Effectiveness and safety of vericiguat in patients with heart failure and reduced ejection fraction: a narrative review of real-world evidence studies - Escobar, Carlos; Caravaca-Pérez, Pedro; Fernandez Rodriguez, Jose Maria; Gomez-Otero, Ines; Lozano-Bahamonde, Ainara; Pérez-Cabeza, Alejandro I.; Pérez-Silvestre, José; Rafols, Carles; Esteban-Fernández, Alberto (Frontiers in Cardiovascular Medicine, 2025)
Heart failure is associated with a high risk of morbidity, mortality, and healthcare resource use. Its pathophysiology and treatment are complex and involve various neurohormonal systems. Early guideline-directed medical therapy is currently recommended in patients with heart failure with reduced ejection fraction; however, patients continue to be at high risk of rehospitalization and death. The VICTORIA clinical trial compared vericiguat, an oral soluble guanylate cyclase stimulator that restores the nitric oxide pathway, with placebo, added to guideline-recommended treatment. VICTORIA demonstrated a significant benefit compared to standard therapy. Nonetheless, it is essential to understand how vericiguat performs in real-world settings. A narrative literature review was performed to compare the findings of the VICTORIA trial and real-world evidence studies. Real-world evidence was analyzed from almost 6,000 patients. Vericiguat was shown to be associated with improvements in quality of life and New York Heart Association functional class, left ventricular reverse remodeling, and numerically lower rates of heart failure hospitalizations and mortality than in the VICTORIA trial, although it is used in older patients with more comorbidities. Moreover, real-world evidence studies showed these effects to be infrequent and similar to those reported in the VICTORIA trial, with low discontinuation rates, indicating that vericiguat was very well tolerated in a real-world population. We present the most comprehensive review to date on vericiguat in clinical practice, providing an overview of its effects on clinical, biochemical, and imaging parameters. Our findings suggest that vericiguat could be a component in the comprehensive management of heart failure with reduced ejection fraction. However, further specific investigations with longer follow-up and larger samples would enable us to resolve some of the hypotheses put forward in our study.